Strategi Branding Bujang Rimba dalam Membentuk Self Image di Media Sosial - Ghea Grahmaulidya; Dedeh Fardiah (Bandung Conference Series: Journalism, 2023)
Abstract. This study aims to determine the branding strategy used by Bujang Rimba in forming self-image on Instagram social media @bujangrimba_. This goal is divided into three factors, namely communication strategy, branding consistency and relevance and Bujang Rimba's self-image. This study uses a qualitative approach with case study analysis, the theory used to support this research is the Impression Management Theory from Jones & Pittman. Self-presentation by Bujang Rimba provides added value in building branding and self-image. Case study analysis is considered to be the most effective method for exploring how Bujang Rimba's strategy builds their branding. The results of the research show (1) Bujang Rimba has never formed and promoted as a creative agency, but they are running as they are as a group of people who have the same hobbies and activities, as well as references to the same interests. With the concept of their everyday style that is humorous and "eccentric". (2) In maintaining consistency with the brand image that has been created. Bujang Rimba makes wild ideas even wilder with their humorous concept. (3) Bujang Rimba in his social media has relevance to the character of his employees where on Instagram social media Bujang Rimba posts motorbike videos because of his hobby of motorbikes, makes vintage concepts because his employees really like vintage references, and humorous concepts because Bujang Rimba packs a creative agency in an eccentric way. Abstrak. Penelitian ini bertujuan untuk mengetahui strategi branding yang dilakukan Bujang Rimba dalam membentuk self-image di media sosial Instagram @bujangrimba_. Tujuan tersebut terbagi menjadi tiga faktor yaitu strategi komunikasi, konsistensi dan relevansi branding dan self-image Bujang Rimba. Penelitian ini menggunakan pendekatan kualitatif dengan analisis studi kasus, teori yang digunakan sebagai penunjang penelitian ini merupakan Impression Management Theory dari Jones & Pittman. Presentasi diri yang dilakukan oleh Bujang Rimba memberikan nilai lebih dalam membangun branding dan self-image. Analisis studi kasus dianggap menjadi metode paling efektif untuk menulusuri bagaimana strategi Bujang Rimba dalam membangun branding mereka. Hasil peneltian menunjukan (1) Bujang Rimba tidak pernah membentuk dan mempromosikan sebagai creative agency, namun mereka berjalan apa adanya sebagai sekelompok orang yang mempunyai hobi dan kegiatan yang sama, serta referensi ketertarikan yang sama. Dengan konsep gaya mereka sehari-hari yang humor dan “nyeleneh”.(2) Dalam mempertahankan konsistensinya dengan brand image yang sudah dibuat. Bujang Rimba membuat ide liar yang lebih liar dengan konsep humor mereka. (3) Bujang Rimba dalam media sosialnya relevansi dengan karakter karyawannya dimana didalam media sosial Instagram Bujang Rimba memposting video motor karena hobi bermotor, membuat konsep vintage karena karyawannya memang menyukasi referensi vintage, dan konsep humor karena Bujang Rimba mengemas creaetive agency secara nyeleneh.